A review of input and output policies for cereals production in Nepal - Pullabhotla, Hemant; Shreedhar, Ganga; Ganesh-Kumar, Anand; Gulati, Ashok (International Food Policy Research Institute, 2011)
This study examines the existing status, policies, and institutions for promoting agricultural output in Nepal, in particular cereals. In this context, it reviews the policies on agricultural input such as seed, fertilizer, water, agricultural equipment, research and extension, and agricultural credit. It also provides an overview of the policies and programs related to agricultural output marketing and procurement of food grains in Nepal.